Myostatin gene polymorphisms among Belgian Blue Crossbreds in smallholder farms in Malaysia - Kamalludin, Mamat Hamidi; Abdullah, Ummi Noorhakimah; Mohd Nor, Norhariani; Goh, Yong Meng; Abu Bakar, Amie Marini; O., Mohd. Firdaus; R., Suriaty (Jabatan Perkhidmatan Veterinar, 2024)
Beef cattle's growth phenotype is linked to their productive cycles determined by the functional group of genes. The candidate gene approach examines genes with subtle effects involved in underlying growth physiological pathways. The double-muscling trait is associated with the highly muscular double- muscled continental breed Belgian Blue caused by polymorphisms specifically myostatin gene mutations (deletions). The trait is integrated into tropical beef cattle herds, resulting in excellent economic value and meat production. The Belgian Blue breed and its crossbreds frequently obtain dressing percentages greater than 60 %, making it a feasible option for farmers who wish to produce leaner meat. Polymerase chain reaction (PCR) and Sanger sequencing analysis were utilized in this study. The objective is to detect specific mutations in Belgian Blue crossbred offspring from Malaysian smallholder beef cattle farming, confirming the genetic basis of enhanced phenotypes and growth projections. 11-base pair (bp), 10-bp, and 6-bp nucleotide deletions were discovered among the Belgian Blue crossbred offspring at various nucleotide (nt) locations. All findings were validated with a beef cattle double-muscling-related literature review. The results offer valuable insights for smallholder farmers, policymakers, and researchers, allowing informed decisions about double-muscling traits and their genetic material utilization in tropical and Malaysian contexts.